2017
DOI: 10.1097/sap.0000000000000837
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium abscessus Infection After Facial Injection With Autologous Fat

Abstract: We report a case of Mycobacterium abscessus infection in a 29-year-old woman after facial injection with autologous fat. Nineteen months previously, she received a facial surgery of autologous fat injection with the fat harvested from her inner thigh. On examination, she had multiple painful and fluctuant abscesses associated with local pyrexia in her bilateral temporal and lower orbital regions. A B ultrasound revealed multiple fat liquefaction in her bilateral temporal and lower orbital regions. The acid-fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…To meet the challenge of NTM diagnosis and management, we should learn more about it. In Table 1 , previous cases of mycobacterial infections caused by cosmetic performance are reviewed[ 2 - 4 , 6 - 14 ], the results of which are consistent with the previous studies[ 1 ]. It is common to be seen in female patients aged 25 to 45 years.…”
Section: Discussionsupporting
confidence: 83%
“…To meet the challenge of NTM diagnosis and management, we should learn more about it. In Table 1 , previous cases of mycobacterial infections caused by cosmetic performance are reviewed[ 2 - 4 , 6 - 14 ], the results of which are consistent with the previous studies[ 1 ]. It is common to be seen in female patients aged 25 to 45 years.…”
Section: Discussionsupporting
confidence: 83%
“…The present three-year study found that M. marinum infections were predominant over other mycobacterial species in causing cutaneous mycobacterial infections, a trend that has been previously reported ( Mei et al., 2019 ). The surge of M. abscessus infection among young women, with the emergence of diverse unscheduled cosmetic infections, made it the second most causative pathogen of cutaneous mycobacterial infections ( Eustace et al., 2016 , Yang et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Blood examination showed normal ALT, total bilirubin levels, and electrolyte levels [20,22,23]. However, on one hand, some studies indicated normal levels of white blood count, and other studies showed a mild elevation in the other hand [19,[22][23][24][25][26][27]. The level of C-reactive protein was also normal in some investigations [19,[22][23][24][25].…”
Section: Paraclinical Characteristicsmentioning
confidence: 95%
“…On ultrasound results, there could be scattered abscesses, fluid fat foci, or heterogeneous irregulatory and hypoechoic injuries [22,24,27,[34][35][36]. Histopathologic images showed ulcerous or granular lesions [23,34,37,38].…”
Section: Paraclinical Characteristicsmentioning
confidence: 99%